FC 065PREDICTING OUTCOMES IN ANCA ASSOCIATED VASCULITIS: THE COMPLETE SCOTTISH EXPERIENCE. (29th May 2021) - McGovern, Dominic; Lees, Jennifer; Kidder, Dana; Smith, James; Traynor, Jamie; Dhaun, Neeraj; Hunter, Robert; Joss, Nicola; Kelly, Michael; MacKinnon, Malcolm; Cousland, Zoe; Shiell, Kate; et al.
Abstract: Background and Aims: Outcomes in ANCA vasculitis remain difficult to predict and therapeutic decision-making can be challenging. We aimed to establish if a renal risk score (RRS) could predict outcomes in this population. Method: The Scottish Renal Biopsy Registry is a complete national dataset of all renal biopsies performed in Scotland. Those who had a first renal biopsy between 01/01/2014 and 31/12/2017 with evidence of ANCA vasculitis were included. Demographic data, treatment regimens, episodes of relapse and patient and kidney survival were recorded, retrospectively. The RRS was calculated using the system proposed by Brix et al (1). Each patient was categorised according to % of normal glomeruli (N0 >25%, N1 10 to 25%, N2 <10%), % of tubular atrophy/interstitial fibrosis (T0 ≤25%, T1 >25%) and eGFR (CKD-EPI) at time of biopsy (eGFR: G0 >15 mL/min/1.73 m 2, G1 ≤15 mL/min/1.73 m 2 ). Individual scores were summated and patients defined as low, medium or high risk. Cox proportional hazard models were created for survival to ESKD, relapse and death, stratified by risk category. Analyses were conducted using R statistical software. Results: Two-hundred and forty-six patients with biopsy proven ANCA vasculitis were identified. Fifty percent (n=123), 46% (n=112) and 5% (n=11) were stratified as low, medium and high risk respectively. Fifty-two percent (n=129) were male and mean age at biopsy was 66.7±12.2 years. This was similar across the risk categories. Mean eGFR was lower in the high-risk category (High risk 8.6±6.1 'v' Low risk 45.7±26.0 ml/min/1.73m 2, p<0.001) and proteinuria was higher (High risk 405 (IQR 170-767) 'v' Low risk 81 (IQR 41-155) mg/mmol, p<0.001). Thirty-seven percent (n=91) were PR3 antigen positive, 2% (n=5) had dual positivity. In the high risk category, 8 (73%) were PR3 or dual positive. Eighteen (n=7%) patients experienced pulmonary haemorrhage; representation similar across all risk categories. Those categorised as medium or high risk were more likely to receive plasma exchange and/or haemodialysis at presentation (p<0.001) compared with the low risk category. Overall, 16% (n=40) of patients relapsed with a trend to higher risk of relapse in the low risk group (27% of these patients, p=0.05). Thirty seven (15%) patients developed ESKD. Cox proportional hazard model for development of ESKD (Figure 1 ) shows that those in high risk 'v' low risk category were more likely to reach ESKD (HR 124.8, 95% CI 26.4-590.3, p<0.001). Patient survival was similar between risk categories. Conclusion: A simple RRS, using routinely reported data, in patients with renal biopsy proven ANCA vasculitis can help to predict development of ESKD. It may also be predictive of future relapse in those with a lower RRS, most likely explained by reduced irreversible damage in this group. The RRS could inform monitoring and treatment decisions. Whilst the numbers are small, a unique strength of this data is that it is based on a complete national dataset making it less susceptible to bias from regional variations in diagnostic and therapeutic practice.